GOVERNMENT'S STRATEGY TO OVERCOME THE IMPACT OF FISCAL AND MONETARY POLICY ON THE INDONESIAN ECONOMY - Nabila Aqila Ghania; Farhan, Farhan; Hanifah Rahmadhani; Meta Eriska; Jenifer; A. Rahman; Sandes Pratama (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
The government's strategy was previously under pressure to improve the economy, one of which is the implementation of fiscal policy. This is because the Covid-19 pandemic in previous years had an impact on all sectors, especially the financial sector. Now with its fiscal policy adjusting between government revenue and spending. Part of the government's fiscal policy during the pandemic, namely the tax relief program aimed at easing the burden on taxpayers and reorienting the 2020 State Budget to increase government spending. Through in-depth research and analysis of the government's strategy for overcoming the impact of fiscal and monetary policies on the economy, it is hoped that a better understanding of government actions in encouraging inclusive and sustainable economic growth in the Indonesian economy will be provided.